Occupational Therapy for Adults with Overweight and Obesity: Mapping Interventions Involving Occupational Therapists - Svetlana Solgaard Nielsen; Jeanette Reffstrup Christensen (Hindawi-Wiley, 2018)
Background. Worldwide obesity rates are increasing. The effectiveness of occupational therapy in overweight and obese adults has not yet been clarified. Objectives. The scoping review aimed at examining the evidence on interventions involving occupational therapists in the treatment of adults with overweight and obesity. Methods. Data on interventions involving occupational therapists and reporting on lifestyle-related outcomes in overweight and obese adults was extracted from the databases Cochrane, PubMed, CINAHL, and Embase, including hand and reference search. The scoping review methodology of Arksey and O'Malley was used. Conclusions were based on numerical and narrative analysis. Results. Thirteen articles reporting on eleven studies met the inclusion criteria. Several studies showed significant weight loss. However, the studies possessed high heterogeneity and showed insufficient explication of the role and contribution of occupational therapy to the outcomes. Conclusions. The interventions with involvement of occupational therapists were suggested to help short-term weight loss. Occupational therapists contributed to the outcomes with a holistic approach, educating on the role of activity, providing technological support, and promoting enjoyment of being active. There is a need for further documentation of the effectiveness, role, and contributions of occupational therapy in the treatment of overweight and obese adults in all settings.